Challenges in Providing Treatment and Care for Viral Hepatitis among Individuals Co-Infected with HIV in Resource-Limited Settings - Wirach Maek-a-Nantawat; Anchalee Avihingsanon; Pirapon June Ohata (AIDS Research and Treatment)
Hepatitis B and C infections are prevalent among HIV-infected individuals with different epidemiologic profiles, modes of transmission, natural histories, and treatments. Southeast Asian countries are classified as “highly prevalent zones,” with a rate of hepatitis B and C coinfection in people living with HIV/AIDS of approximately 3.2–11%. Majority of hepatitis B coinfection is of genotype C. Most of the patients infected with hepatitis C in Thailand have genotype 3 which is significantly related to intravenous drug use whereas, in Vietnam, it is genotype 6. The options for antiretroviral drugs are limited and rely on global funds and research facilities. Only HBV treatment is available for free through the national health scheme. Screening tests for HBV and HCV prior to commencing antiretroviral treatment are low. Insufficient concern on hepatitis-virus-related liver malignancy and long-term hepatic morbidities is noted. Cost-effective HCV treatment can be incorporated into the national health program for those who need it by utilizing data obtained from clinical research studies. For example, patients infected with HCV genotype 2/3 with a certain IL-28B polymorphism can be treated with a shorter course of interferon and ribavirin which can also help reduce costs.